2017
DOI: 10.1186/s12909-017-0939-7
|View full text |Cite|
|
Sign up to set email alerts
|

Medical students can teach communication skills – a mixed methods study of cross-year peer tutoring

Abstract: BackgroundCross-year peer tutoring (CYPT) of medical students is recognized as an effective learning tool. The aim of this study is to investigate the non-inferiority of the objective outcome of medical interview training with CYPT compared with the results of faculty-led training (FLT), and to explore qualitatively the educational benefits of CYPT.MethodsWe conducted a convergent mixed methods study including a randomized controlled non-inferiority trial and two focus groups. For the CYPT group, teaching was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
(35 reference statements)
1
21
0
1
Order By: Relevance
“…One systematic review suggested that educational interventions, such as structured reading programs and a “boot camp” curriculum, were effective for improving the scores in in-training examinations in surgery [ 26 ]. Thus, the faculty may be able to provide this peer learning opportunity for trainees requiring special support by collaborating with potential leaders with experience of scholarly activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review suggested that educational interventions, such as structured reading programs and a “boot camp” curriculum, were effective for improving the scores in in-training examinations in surgery [ 26 ]. Thus, the faculty may be able to provide this peer learning opportunity for trainees requiring special support by collaborating with potential leaders with experience of scholarly activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To deal with this issue, a peer learning training system has been implemented in an anesthesiology residency in the United States (17) . Peer learning, in which trainees teach each other in small groups, provides trainees with a psychologically “safe” environment to learn and facilitate their deeper understanding of educational contents and reflections (18) . This teaching and learning methodology can create a mutual mentorship environment for both young and experienced researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the word “Tutee” on the right-hand side of Fig. 3 should read “Tutor”.…”
Section: Correctionmentioning
confidence: 99%